Twiddler’s syndrome after implantation of baroreflex activation therapy: a case report - Dalos, Daniel (Eur Heart J Case Rep, 2021)
BACKGROUND: Twiddler’s syndrome is a rare complication after implantation of cardiac pacemakers or cardioverter-defibrillators that usually occurs within the first year after the procedure. However, it has not yet been described following implantation of baroreflex activation therapy (BAT). CASE SUMMARY: A 61-year-old female patient was referred to the cardiology outpatient clinic due to uncontrolled arterial hypertension despite maximal doses of several established drugs. Therefore, right-sided BAT implantation was successfully performed in February 2017 with good clinical response. Because of sustained neck pain at the site of stimulator, surgical revision was performed in November 2019 including a switch of the lead to the contralateral position. Approximately 1 month later, Twiddler’s syndrome was identified on the basis of recurrent pain at the generator site necessitating pocket-revision, however, the lead was only untwisted but not replaced. A few weeks afterwards, unfortunately, lead revision was indispensable due to lead fracture. DISCUSSION: This case presents the uncommon phenomenon of Twiddler’s syndrome after BAT implantation. In addition, the commonly twisted lead should always be replaced as well during surgical pocket-revision in order to ensure proper long-term function.